Nonparametric identification of dynamic models with unobserved state variables - Yingyao Hu; Matthew Shum (The Johns Hopkins University, Department of Economics, 2008)
We consider the identification of a Markov process Wt,Xt* for t = 1, 2, ... , T when only Wt for t = 1, 2, ... , T is observed. In structural dynamic models, Wt denotes the sequence of choice variables and observed state variables of an optimizing agent, while Xt* denotes the sequence of serially correlated unobserved state variables. The Markov setting allows the distribution of the unobserved state variable Xt* to depend on Wt-1 and Xt-1*. We show that the joint distribution f Wt, Xt* | Wt-1, Xt-1* is identified from the observed distribution f Wt+1, Wt | Wt-1, Wt-2, Wt-3 under reasonable assumptions. Identification of f Wt, Xt*, Wt-1, Xt-1* is a crucial input in methodologies for estimating dynamic models based on the conditional-choice-probability (CCP) approach pioneered by Hotz and Miller.
Keywords: 330; Markovscher Prozess; Ökonometrie